SYSTEMATIC LITERATUR REVIEW : PERAN COOPERATIVE LEARNING DALAM MENINGKATKAN SELF-EFFICACY PADA PEMBELAJARAN MATEMATIKA - Rahel Gebi Rianty Siahaan; Heni Pujiastuti; Nurul Anriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
In mathematics learning, students have low self-efficacy, which results in low engagement and learning outcomes. One method that can be used to address this problem is by implementing a cooperative learning model. The purpose of this study is to analyze various types of cooperative learning, discover how cooperative learning helps students become more independent, and find errors in previous research. A Systematic Literature Review (SLR) is the method used. SLR examines relevant scientific articles from the last five years (2020–2025) collected from various databases such as Google Scholar, ERIC, ScienceDirect, and SINTA. The results of the study indicate that cooperative learning significantly improves students' self-efficacy. Cooperative learning such as Division of Student Team Achievement (STAD), Group Investigation (GI), Think Pair Share (TPS), and Teams Games Tournament (TGT) have been shown to increase students' self-confidence because they provide significant learning experiences, group collaboration, and social interaction. In addition, learning together improves cognitive abilities such as reasoning, conceptual understanding, and mathematics learning outcomes. Because student self-efficacy increases unevenly, teachers must employ appropriate learning strategies. Consequently, cooperative learning is recommended as an effective learning model for improving the quality of mathematics learning.